2010
DOI: 10.1136/pgmj.2009.090399
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in rheumatoid arthritis

Abstract: Management of rheumatoid arthritis (RA) has radically changed over the last decade. Diagnostic methods have improved with availability of highly specific tests such as antibody to cyclic citrullinated peptide (specificity approximately 96%), and introduction of advanced imaging modalities such as ultrasound and magnetic resonance imaging to facilitate earlier diagnosis. The current aim of management is to achieve remission and prevent joint damage. In order to achieve this goal, inflammation is suppressed as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 92 publications
2
10
0
1
Order By: Relevance
“…Prevenir dano articular e conseguir remissão têm se tornado alvos possíveis de serem alcançados. Embora agentes biológicos como os anti-TNF-α tenham demonstrado atuar de maneira positiva na diminuição da aterosclerose, ainda não se demonstrou redução da taxa de mortalidade em AR nos últimos 50 anos (63).…”
Section: Manifestações Clínicasunclassified
“…Prevenir dano articular e conseguir remissão têm se tornado alvos possíveis de serem alcançados. Embora agentes biológicos como os anti-TNF-α tenham demonstrado atuar de maneira positiva na diminuição da aterosclerose, ainda não se demonstrou redução da taxa de mortalidade em AR nos últimos 50 anos (63).…”
Section: Manifestações Clínicasunclassified
“…Both TJC and SJC, although representing the clinical features of inflammation, can significantly be influenced by the use of non‐steroidal anti‐inflammatory drugs (NSAIDs), patient's anxiety and depression, and have significant inter‐observer variability . Studies have indicated that the number of erosions and deformities are proportional to the persistence of inflammation, as well as its duration . Drawing a corollary from diabetes mellitus (DM) where the basic target is good control of plasma/blood sugar, the aim and scope of measurement of RA is inflammation.…”
Section: Drifting Away From All Definitionsmentioning
confidence: 99%
“…oldhamii have been used as a folk medicine to treat rheumatoid arthritis (RA) in southern China . It is thought that tumor necrosis factor α (TNFα), interleukin-1 (IL-1), and interleukin-2 (IL-2) play important roles in the pathophysiology of RA, and therapies targeting these proteins have shown positive outcomes in treatment of RA . Ge et al examined the inhibitory effects of aristolactam GI ( 1 ) upon the release of TNFα and IL-6 induced by lipopolysaccharide in murine macrophage RAW264 cell cultures, and it was shown that aristolactam GI ( 1 ) exhibited statistically significant inhibition in the production of both TNFα and IL-6.…”
Section: Introductionmentioning
confidence: 99%